The imposition of Countervailing Duties in the Framework of the Agreements of the World Trade Organization: Issues of Special Interest on the de jure Specificity in front of European Subsidies in Agricultural Matters - García Guerrero, David (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
World Trade Organization Members may establish countervailing duties on products imported into their territory that have been the subject of specific subsidies and have caused injury to a domestic industry. These taxes are framed in International Tax Law. Countervailing duties is especially complex and has not been treated in depth by the tax doctrine compared to other issues of international taxation. For this reason, an analysis of certain elements that serve to determine the existence or absence of the de jure specificity of the subsidies of the Common Agricultural Policy of the European Union is proposed. It is a key factor in imposing countervailing duties. However, it should start from a necessary contextualization of customs matters within International Tax Law.